2011
DOI: 10.1007/s00125-011-2235-0
|View full text |Cite
|
Sign up to set email alerts
|

No evidence for a causal link between uric acid and type 2 diabetes: a Mendelian randomisation approach

Abstract: Aims/hypothesis Epidemiological and experimental evidence suggests that uric acid has a role in the aetiology of type 2 diabetes. Using a Mendelian randomisation approach, we investigated whether there is evidence for a causal role of serum uric acid for development of type 2 diabetes. Methods We examined the associations of serum-uric-acidraising alleles of eight common variants recently identified in genome-wide association studies and summarised this in a genetic score with type 2 diabetes in case-control s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
68
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(80 citation statements)
references
References 38 publications
9
68
2
1
Order By: Relevance
“…This is similar to the study by Sudhindra Rao, 14 M Modan, 15 Nakanishi, 16 Abbas D, 4 While R Pfister 17 found no correlation and Pavani Bandaru 18 found inverse correlation of level of uric acid and duration of diabetes. Our study confirms the finding of other studies that uric acid increases as the duration of diabetes increases.…”
Section: Discussionsupporting
confidence: 89%
“…This is similar to the study by Sudhindra Rao, 14 M Modan, 15 Nakanishi, 16 Abbas D, 4 While R Pfister 17 found no correlation and Pavani Bandaru 18 found inverse correlation of level of uric acid and duration of diabetes. Our study confirms the finding of other studies that uric acid increases as the duration of diabetes increases.…”
Section: Discussionsupporting
confidence: 89%
“…In contrast to previous observational findings, there is no strong evidence for causal associations between uric acid and ischemic heart disease or blood pressure [41]. The approach has also demonstrated that elevated serum uric acid is a consequence, rather than a cause, of adiposity [42,43], and is not a cause of type 2 diabetes [44] or metabolic syndrome [45]. Although we could not rely on Mendelian randomization due to the lack of genetic data, these reports and our results suggest that the association between uric acid levels and reduced kidney function is far more complex than what was previously thought.…”
Section: Discussionmentioning
confidence: 39%
“…However, the present study showed that increased concentrations of SUA did not lead to the increased glucose concentration (HR = 1.34, 95% CI, 0.93-1.95, P = NS). Some researchers also reported no association between them while others suggested a negative relationship [21,22]. Additionally, another previous study reported an inverse U-shaped association between fasting glucose and SUA concentrations, suggesting the positively relationship only existed when SUA concentration was b 8.0 μmol/l [23].…”
Section: Discussionmentioning
confidence: 87%
“…Yuri et al demonstrated that hyperuricemia induced oxidative stress in adiocytes [24], and insulin resistance causing the glucose metabolic disorder was partly mediated by oxidative stress [25]. Nonetheless, substantial evidence of confounding was found modifying the causality [22]. Other covariates, such as hypertension, alcohol drinking, BMI and Table 1 baseline characteristics of study population stratified for the absence and presence of MetS.…”
Section: Discussionmentioning
confidence: 96%